EFEKTIFITAS PERATURAN MENTERI HUKUM DAN HAM TENTANG ASIMILASI NARAPIDANA KELAS I CIPINANG DALAM RANGKA COVID-19 - Anna Maria Magdalenna Pridag; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
In early November 2019 in the city of Wuhan, China, it was suspected that the beginning of an outbreak of a virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which came from imported frozen food raw materials that entered the wet market area of Wuhan City, but according to a study that has been conducted by experts which resulted that the covid-19 virus originated from a local case where covid-19 spreads around the world one after another by means of transmission which is called an import case from outside the area of origin or local transmission between residents while in Indonesia itself, the Covid-19 virus outbreak entered in early 2020, in which the virus attacks the human respiratory system regardless of human age. The covid-19 virus causes distance between humans and another which causes many countries to make a policy, namely lockdown, while the Indonesian government makes policies in the form of Large-Scale Social Restrictions (PSBB). This PSBB is a policy that must be obeyed by all citizens of the Republic of Indonesia, especially prisons, but the condition of correctional institutions in Indonesia is currently experiencing overcapacity, causing the Ministry of Law and Human Rights to make a policy, namely the Regulation of the Minister of Law and Human Rights.